2016
DOI: 10.1007/s00415-016-8259-0
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal α-synuclein in α-synuclein aggregation disorders: tau/α-synuclein ratio as potential biomarker for dementia with Lewy bodies

Abstract: Several studies have addressed the utility of cerebrospinal (CSF) α-synuclein levels as a potential biomarker of α-synuclein aggregation disorders. However, its relevance in the differential diagnostic context of neurodegenerative and movement disorders is still a contentious subject. Here, we report total CSF α-synuclein levels in a cohort of clinically diagnosed α-synuclein-related disorders encompassing Parkinson's disease, Parkinson's disease dementia, dementia with Lewy bodies and multiple system atrophy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 45 publications
6
30
0
2
Order By: Relevance
“…This was further substantiated when we found that in a bilateral comparison, the combination of o‐α‐syn and tau optimally discriminates DLB from AD. Taken together with the results of previous studies, our observations underline the potential of combining α‐syn species with other biomarkers like Aβ 1‐42 , tau, and p‐tau to improve the differential diagnosis of DLB. Other, yet to be discovered potential biomarker candidates or posttranslationally modified α‐syn species, may also be useful for this purpose.…”
Section: Discussionsupporting
confidence: 81%
“…This was further substantiated when we found that in a bilateral comparison, the combination of o‐α‐syn and tau optimally discriminates DLB from AD. Taken together with the results of previous studies, our observations underline the potential of combining α‐syn species with other biomarkers like Aβ 1‐42 , tau, and p‐tau to improve the differential diagnosis of DLB. Other, yet to be discovered potential biomarker candidates or posttranslationally modified α‐syn species, may also be useful for this purpose.…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with our hypothesis, the serum levels of sLAG‐3 in PD patients increased when compared with NC in the present study. We also found that serum sLAG‐3 in ET is lower than in PD and similar to levels in NC, in agreement with previous findings that α‐syn level in both cerebrospinal fluid (CSF) and peripheral blood is similar in ET and NC . However, the risk of developing PD in ET is higher than in healthy people .…”
Section: Discussionsupporting
confidence: 91%
“…Tau and α‐syn interact and promote each other's aggregation, and co‐occurrence of tau and t‐α‐syn inclusions are frequent in PD, DLB and AD . A positive correlation was found between t‐α‐syn and t‐tau which is in line with previous studies . Two previous studies have reported an improved diagnostic performance using the t‐tau/t‐α‐syn ratio in distinguishing PD from controls .…”
Section: Discussionsupporting
confidence: 90%